Analisis Kebijakan Inklusif terhadap Dinamika Lingkungan Kerja KRI : Tinjauan Kualitatif Manajemen SDM pada Satgas MTF UNIFIL - Apsari, Windi; Umiyati, Sri; Sulistyanto, Sulistyanto (Universitas Trunojoyo Madura, 2025)
United Nations Security Council Resolution (UNSCR) 1325 (2000) emphasizes the importance of women’s participation and involvement in global peacekeeping missions. As part of its implementation, the Government of Indonesia, through the Indonesian Navy, issued an inclusive human resource (HR) policy by deploying members of the Indonesian Navy Women’s Corps (Kowal) in the Maritime Task Force (MTF) of the United Nations Interim Force in Lebanon (UNIFIL) beginning in 2021. Previously, from 2009 to 2020, all MTF UNIFIL personnel were male, creating a masculine work environment aboard Indonesian warships (KRI). This study aims to analyze the impact of the inclusive HR policy on the work environment dynamics in KRI, identify supporting and inhibiting factors, and examine male soldiers’ perceptions of the presence of Kowal. The research employs a qualitative descriptive method using interviews, observations, and documentation. The findings indicate that the presence of Kowal has brought positive changes to the work environment while maintaining the existing systems and organizational culture. Male personnel generally responded positively to their presence; however, the implementation requires strict gender-based regulations. The study recommends strengthening HR curricula with a focus on gender equality, adjusting the quota of Kowal according to KRI facilities, and formulating written gender-based regulations within the MTF UNIFIL.